The PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, FINANCIAL DISTRESS, DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSAEFEK INDONESIA PERIODE 2018-2021: PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE, FINANCIAL DISTRESS, DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI - Purnamasari, Dian Indri; Tashya, Angel (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research aims to empirically examine the impact of managerial ownership, leverage, financial distress, and profitability on accounting conservatism in mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2021. The data used in this study is obtained from secondary data sources accessed through the company's annual reports and other websites. The research population consists of mining sector companies listed on the Indonesia Stock Exchange during the period of 2018-2021. The sampling technique used in this study is the purposive sampling method, which resulted in 24 out of the total 49 mining companies that have managerial ownership. A total of 24 companies were selected as samples over a period of 4 years, resulting in 96 financial report data samples. The data was processed using the IBM SPSS Statistic 24 application. The results of this study indicate that managerial ownership, leverage, financial distress, and profitability have an impact on accounting conservatism. Therefore, further studies are needed to expand these factors so that the findings can be more comprehensive. As a recommendation from this study, it is expected that companies can maintain and enhance the principle of accounting conservatism to reduce information asymmetry among shareholders, investors, or creditors. Keywords: Managerial Ownership, Leverage, Financial Distress, Profitability, Accounting Conservatism.